Case Report: Full-house renal-limited lupus-like nephritis in pregnancy - Wilkinson, Lucille Jane; Stauder, Sally; Culpepper, Brady; Ibrahim, Jalal; Pantangi, Vivekanand; Simhadri, Prathap Kumar (Frontiers in Nephrology, 2025)
Lupus nephropathy is a common manifestation of systemic lupus erythematosus (SLE), with immune-mediated inflammatory damage to the glomerulus leading to acute kidney injury, chronic kidney disease, and end-stage renal disease. Occasionally, patients present with renal-limited lupus nephropathy with classic full-house staining on immunofluorescence and no signs of systemic lupus. Limited data are available on renal-limited “lupus-like nephropathy” in pregnancy. A 24-year-old G1P0 woman at 14 weeks of gestation was referred to nephrology for further evaluation of 8.4g proteinuria. She was found to be ANA negative with a decreased C1q level and a renal biopsy revealing membranous nephropathy. Immunofluorescence staining was positive for IgG, IgA, IgM, C3, and C1Q, consistent with full-house pattern. She was started on 500 mg pulse dose methylprednisolone for 3 days, which was gradually tapered to 5 mg daily, and cyclosporine 75 mg BID. She delivered a healthy baby via induction at 36 weeks. Six-month follow-up revealed 1g protein on 24-hour urine collection, normal C3/C4 levels, and no signs of SLE. This case report adds to the literature discussing renal-limited “lupus-like nephropathy” in pregnancy and helps guide further management of this condition.